PENGARUH STRATEGI HEURISTIK KRULICK RUDNICK BERBASIS ETNOMATEMATIKA TERHADAP KEMAMPUAN REPRERESENTASI GEOMETRI - Kadir Kadir; Eva Musyrifah; Ruspa Dewi Safitri (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2019)
The purpose of this research is to analyze the effect of Krulick Rudnick Heuristic Strategy based on ethnomathematics on student geometric representation skill (GRS). The research conductes at Junior High School in Jakarta in Academic Year 2018/2019. This research was quasi-experimental method with randomized posttest only control group, which is involve 27 students in experimental class and 25 students in control class that choosen by cluster random sampling technique. The data collecting for GRS used by using the test. The result of research revealed that student’s GRS taught by Krulick Rudnick’s Heuristic strategy based on ethnomathematics is higher than those taught by expository strategy. That skills include visual, symbolic, and verbal indicators. Ethnomatematics involved include culture of bamboo fishtrap (bubu), transplantation of coral reefs, mangrove conservation, processed fish food, fishing activities (manyang), tourist resorts, historic building, and food served in traditional traditions (sea parties). The conclusion of this show that the use of Krulik Rudnick heuristic strategy based on etnomathematics is more effective in enhanching students’ GRS compared with an expository strategy. (η2=0,102).